Detection and molecular status of Isospora sp. from the domestic pigeon (Columba livia domestica). Issue 5 (October 2017) - Matsubara, Ryuma; Fukuda, Yasuhiro; Murakoshi, Fumi; Nomura, Osamu; Suzuki, Toru; Tada, Chika; Nakai, Yutaka
Abstract: The domestic pigeon, Columba livia domestica, is reared for meat production, as a pet, or for racing. Few reports have characterized the parasitic protists from the genus Isospora isolated from Columbiformes. We detected Isospora -like oocysts from C. livia reared for racing. The oocyst contained two sporocysts, and each sporocyst included four sporozoites. The sporulated oocysts ( n = 4) were spherical; their mean diameters were 25.6 (24.0–27.2) × 24.7 (23.4–26.0) μm. Micropyles, polar granules, and oocyst residuum were absent. The mean length and width of the sporocysts ( n = 8) were 19.5 (18.5–20.5) and 11.2 (10.2–12.1) μm, respectively. Stieda and sub-Stieda bodies were observed. Single-oocyst PCR revealed two different 18S rRNA gene sequences and one 28S rRNA gene sequence in a single oocyst of Isospora sp. Based on a phylogenetic analysis of the 18S rRNA gene, the two sequences made a group which fell within a cluster of known avian Isospora species. A tree based on the 28S rRNA gene sequence indicated that sequences from the pigeon Isospora sp. fell within a cluster of avian Isospora species. Both trees failed to clarify the phylogenetic relationships among the avian Isospora species due to limited resolution. Because the morphological description of Isospora sp. is based on only four oocysts, Isospora sp. is not proposed as a novel species here. This is the first description of Isospora sp. isolated from the domestic pigeon C. livia . Graphical abstract: Highlights: Isospora sp. oocysts were detected from feces of the domestic pigeon Columba livia . Oocysts 25.6 × 24.7 μm, no micropyles, polar granules nor oocyst residuum Sporocyst 19.5 × 11.2 μm, Stieda and sub-Stieda bodies observed. Morphology distinct from I. gallicolumbae, the only known pigeon Isospora